Zarys działalności oświatowej Lubelskiego Towarzystwa Rolniczego w latach 1905–1914 - Przegaliński, Andrzej (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The article presents the educational activity of Lublin’s Agricultural Company (LAC). The origin of the organization reached the last years of 19th century and the works of Agricultural Association (Syndicate) in Lublin. In the context of activity that LAC used to lead, it is understandable to characterize its achievements on the field of improving both cultivation and rural industry. The LAC realized the program that was mainly directed to the peasant community. Under auspices of LAC were organized local farm associations, shops, various courses, competitions and exhibitions. In the year of 1907 the LAC established The Lower Men’s Agricultural School in Nałęczów. All mentioned above ventures had important meaning for peasants and without a doubt helped to progress the peasant production, cultivation and animal husbandry.